2021
DOI: 10.5194/acp-21-989-2021
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft-based observation of meteoric material in lower-stratospheric aerosol particles between 15 and 68° N

Abstract: Abstract. We analyse aerosol particle composition measurements from five research missions between 2014 and 2018 to assess the meridional extent of particles containing meteoric material in the upper troposphere and lower stratosphere (UTLS). Measurements from the Jungfraujoch mountaintop site and a low-altitude aircraft mission show that meteoric material is also present within middle- and lower-tropospheric aerosol but within only a very small proportion of particles. For both the UTLS campaigns and the lowe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 126 publications
(180 reference statements)
0
26
0
Order By: Relevance
“…None of these events were targeted during the flights. Such variations in the stratospheric aerosol layer are important for both heterogeneous chemistry (Solomon et al, 1996) and climate (Solomon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these events were targeted during the flights. Such variations in the stratospheric aerosol layer are important for both heterogeneous chemistry (Solomon et al, 1996) and climate (Solomon et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hofmann et al (2009) found an increasing trend after 2000, and Friberg et al (2014) found an increasing trend from 1999 to 2008. There has been recog-8916 D. M. Murphy et al: The size and composition of aerosol particles in the stratosphere nition that moderate volcanic eruptions frequently influence the stratospheric aerosol and true non-volcanic "background" concentrations are not necessarily present just because there has been no Pinatubo-scale eruption (Solomon et al, 1996. Different altitudes may exhibit different trends (Khaykin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in situ instrumentation can distinguish various types of aerosol particles in the stratosphere and determine their relative abundance. In the background lower stratosphere, a large fraction of SSA droplets contains inclusions of meteoritic and/or organic material (Murphy et al, 2014;Schneider et al, 2021). The solid inclusions could have important implications for the ability of particles to act as freezing nuclei for PSCs.…”
Section: The Possible Origin Of Heterogeneous Nat Nucleimentioning
confidence: 99%
“…This The scientific basis of PSC formation has been introduced in Section 3, with Figure 26 showing the different formation pathways of the individual PSC compositions: The nucleation of ice can occur homogeneously or heterogeneously on preexisting particles, whereas the nucleation of NAT must occur heterogeneously on solid nuclei. Recent studies have demonstrated the importance of heterogeneous nucleation on foreign nuclei, but not much is known about these nuclei other than they may consist of meteoritic or a variety of other materials (Ebert et al, 2016;Schneider et al, 2021;Schütze et al, 2017). Therefore, the simulation of heterogeneous PSC formation requires certain assumptions to be made.…”
Section: Parameterizations Of Pscs In Global Modelsmentioning
confidence: 99%
“…The meteoric material could act as sink for gaseous H 2 SO 4 . Detected meteoric dust in the UTLS (Schneider et al, 2021) also suggests that it has to be incorporated into the model to reproduce observations of higher aerosol concentrations in the upper stratosphere. Thus, the aerosol extinction for the upper stratosphere and mesosphere is underestimated in model simulations without implementation of meteoric material in the radiation calculations.…”
Section: Discussionmentioning
confidence: 99%